Erosion, caries and rampant caries in preschool children in Jeddah, Saudi Arabia - Al-Malik MI, Holt RD, Bedi R. (Blackwell Synergy, 2002)
The objective of this study was to determine the prevalence of dental erosion in preschool children in Jeddah, Saudi Arabia, and to relate this to caries and rampant caries in the same children. Methods: A sample of 987 children (2–5 years) was drawn from 17 kindergartens.